CULTIVATION AND PLANTING OF RED GINGER (ZINGIBER OFFICINALE VAR.RUBRUM) USING BAG CULTURE TECHNOLOGY DURING THE NEW NORMAL PERIOD IN MEASLES VILLAGE KADUHEJO DISTRICT PANDEGLANG - Alhamidi, Edi Muhammad Abduh; Darojat, Wahyu; Rani, Iyun; Wiranto, Wiranto (Nindikayla Institute, 2024)
As a solutive effort in dealing with the impact of the covid-19 pandemic by using land in measles villages. Red ginger cultivation is one of the alternatives in efforts to improve the economy of Small and Medium Micro Enterprises in the countryside. Ginger plants can be used as antibacterial, antioxidant and herbal medicinal ingredients or made immunity-enhancing drinks. The purpose of this devotional activity is to provide counseling of cultivation and processing of red ginger plants. The method is done by cultivating and processing red ginger plants using bag culture technology, planted in polybags. The cultivation of red ginger plants is carried out by students who conduct independent work lectures in partnership with Karang Taruna Desa Measles.